The Impact of Concurrent Use of Diuretics, RAAS Inhibitors with Non-steroidal Anti-inflammatory Drugs â€œTriple Whammyâ€ on Renal Function (Asian Journal of Pharmaceutics (AJP), 2020)
Objective: This study aimed to evaluate the concomitant use of diuretics, angiotensin-converting-enzyme inhibitors/angiotensin receptor blocker (ACEIs/ARBs) and non-steroidal anti-inflammatory drugs, frequently termed asâ€œTriple Whammy,â€ prescribed among out-patients. It also aimed to determine the impact of this combinationon patientsâ€™ renal function. Methodology: A retrospective and observational study was conducted in a hospitallocated in the state of Selangor, Malaysia. Patients who were receiving two or more of triple whammy agents werereviewed and analyzed. The associations between the prescriptions and patientsâ€™ demographics and comorbiditieswere tested using the Chi-square test. On the other hand, a paired sample t-test was used to determine the impactof prescriptions on renal function with a consideration of statistical significance when P < 0.05. Results: Outof 412 prescriptions (60.2% male) were included in this study, 407 prescriptions were containing two of thementioned medication with only 5 prescriptions for triple whammy. The majority of prescriptions had (64.1%)ACEIs/ARBs and diuretics, and it was mainly prescribed to hypertensive patients (98.5%) aged less than 65 yearsold (38.3%). Furthermore, males were more likely to receive this combination of ACEIs/ARB and diuretics thanfemales (P < 0.001) due to the fact that the male gender is considered as a risk factor for cardiovascular conditionsthat require ACEIs/ARBs + diuretics. In addition, there was a statistically significant decrease in CrCl after theserisky combinations were initiated. Conclusion: The prescribing trend of triple whammy during the period of datacollection was low compared to prescriptions of two risky combinations. This is indeed a good predictor of safeprescribing of drugs among physicians, as concomitant use of these three medications may impair renal functions.